PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA YANG DIAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI DAN PEMBELAJARAN PBI DI KELAS VIII MTS UMN AL-WASLIYAH MEDAN TP. 2016/2017 - Indra Jaya (AXIOM : Jurnal Pendidikan dan Matematika, 2017)
The purpose of this study were: 1) To determine the ability of problem solving mathematics students are taught by cooperative learning type TAI in class VIII MTs UMN Al-Washliyah Medan TP.2016 / 2017. 2) To find out the ability of problem solving of mathematics of students taught by PBI learning in class VIII MTs UMN Al-Washliyah Medan TP.2016 / 2017. 3) To know the difference of problem solving ability of student mathematics taught by using cooperative learning model of TAI type and PBI learning in class VIII MTs UMN Al-Washliyah Medan TP.2016 / 2017. This research is quantitative research with quasi experiment research type. The population is all students of class VIII MTs UMN Al-Washliyah Medan TP.2016 / 2017, which amounts to 132 students from 4 classes. While the samples are 2 classes of class VIII-A amounted to 30 students and class VIII-B amounted to 31. Techniques of data collection conducted by observation, tests and documentation. The test instrument used to determine students' mathematical problem solving skills is essay test in the form of post-test. Data analysis was performed by normality test, homogeneity test and hypothesis test using variance analysis (ANAVA). The results of this finding indicate: 1) The ability of problem solving of students mathematics taught by using cooperative learning model type TAI very good. 2) Math problem solving skills of students who are taught using good PBI learning. 3) Students' mathematical problem solving ability on circle material is better if taught with cooperative learning model of TAI type rather than PBI learning in class VIII MTs UMN Al-Washliyah Medan TP.2016 / 2017. The conclusion of this research explains that the problem solving ability of students mathematics which is taught with cooperative learning model of TAI type better than that taught by PBI learning in class VIII MTs UMN Al-Washliyah Medan TP.2016 / 12017.